Does Religiosity Matter in Switching from Conventional to Islamic Insurance? - Novitasari, Evi; Pangaribuan, Christian Haposan (Journal of Multidisciplinary Issues, 2021)
Objective – Despite the fact that Islamic insurance has grown significantly in Muslim countries; the number of market users was still very low compared to its market potential in Indonesia. The purpose of this research is to understand the factors that influence consumers to switch from conventional insurance to Islamic insurance.Methodology – The influential factors being studied in this quantitative research are religiosity and product awareness and employs Qualtrics online survey that was administered to 200 Muslim customers of major life insurance over a period of 3 months (from June until August 2018). The group of population being the object in this study is Muslims who are non-participants of Islamic insurance, the current customers of conventional insurance who has monthly fix income and located in the city of Jakarta and its surroundings.Findings – The results reveal religiosity to have a significant influence on switching attitudes and switching behavior. However, the other tests for the relationship between product awareness and switching attitudes as well as between product awareness and behavioral intention were not supported.Novelty – Although past studies have investigated religiosity and product awareness in the context of switching from conventional to Islamic insurance, none have examined this issue in Indonesia. The paper concludes with the practical implications of the research.